2015
DOI: 10.1021/acs.jpcc.5b01552
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Photoluminescence Properties of Ce3+-Doped Ca2YZr2Al3O12: A Novel Garnet Phosphor for White LEDs

Abstract: A novel garnet phosphor Ca 2 YZr 2 Al 3 O 12 :Ce 3+ (CY-ZA:Ce 3+ ) has been successfully designed and synthesized via the solid state method. The crystal structure, morphology, as well as their photoluminescence properties were investigated in detail. Under nearultraviolet (n-UV) excitation, CYZA:Ce 3+ exhibits cyan to green emission with the maxima from 484 to 503 nm when varying the Ce 3+ concentration. The internal quantum efficiency of the optimal sample is 56%. The concentration quenching of Ce 3+ emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 31 publications
3
45
0
Order By: Relevance
“…There are four types of distinctive cation sites in the LMN unit cell. 39,40 As a result, the incorporation of Mn 4+ into the LMN host may induce defects such as V .. These isolated octahedrons share edges with adjacent ones, constructing the three-dimensional rock salt structure, which provides multiple suitable sites for Mn 4+ doping.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four types of distinctive cation sites in the LMN unit cell. 39,40 As a result, the incorporation of Mn 4+ into the LMN host may induce defects such as V .. These isolated octahedrons share edges with adjacent ones, constructing the three-dimensional rock salt structure, which provides multiple suitable sites for Mn 4+ doping.…”
Section: Resultsmentioning
confidence: 99%
“…So, it can be concluded that the doping Mn 4+ ions may occupy the Nb 5+ sites in the LMN host. 39,40 As a result, the incorporation of Mn 4+ into the LMN host may induce defects such as V ..…”
Section: Resultsmentioning
confidence: 99%
“…However, the preparation of these phosphors is very energy‐intensive, requiring high temperature and high pressure, which leads to the limitation for application in LEDs. For many oxides based green phosphors, such as M 2 SiO 4 (M = Sr, Ca, Ba), they always have disadvantage in thermal stability . Hence, it is imperative to develop a new type of oxide based green phosphors at low temperature to cut cost and have good thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the I + 2 II 2+ P 2 O 7 (I = Li, Na, K, Rb, Cs, II = Mg, Ca, Sr, Ba) (e.g., Li 2 BaP 2 O 7 , K 2 MgP 2 O 7 , Cs 2 M 2+ P 2 O 7 (M 2+ = Ca, Sr), etc.) compound can be synthesized at a lower temperature of no more than 1073 K than aluminates, silicates, and other salts (above 1473 K) . Among this class of host materials, K 2 CaP 2 O 7 (KCPO) has adequately substitutable space (Ca 2+ radii is about 1.00 Å and K + radii is nearly 1.46 or 1.51 Å with seven or eight surrounding O atom) for RE ions.…”
Section: Introductionmentioning
confidence: 99%
“…compound can be synthesized at a lower temperature of no more than 1073 K than aluminates, silicates, and other salts (above 1473 K). 11,[15][16][17][18] Among this class of host materials, K 2 CaP 2 O 7 (KCPO) has adequately substitutable space (Ca 2+ radii is about 1.00 A and K + radii is nearly 1.46 or 1.51 A with seven or eight surrounding O atom) for RE ions. In view of above advantages, KCPO is believed to be an appropriate host substance for luminescent materials.…”
Section: Introductionmentioning
confidence: 99%